Common privacy patterns in video surveillance and smart energy - Bier, Christoph; Krempel, Erik (2012 8th International Conference on Computing and Convergence Technology, 2012)
The issue of incorporating privacy into complex information systems has grown substantially over the past few years. At the same time, the design of converging IT-systems still lacks a structural approach respecting privacy. Similar to software and security engineering, a useful toolkit for system developers would be a set of privacy design patterns. This work evaluates established privacy approaches in video surveillance and smart energy. Common patterns in these two real world scenarios are identified. Based on that, a general structure for a privacy pattern language is proposed.